The comparison of the best practices of the community-based education for living heritage site conservation - Abdul Aziz, Noor Azramalina; Mohd Ariffin, Noor Fazamimah; Ismail, Nor Atiah; Ismail, Sumarni; Alias, Anuar; Utaberta, Nangkula (Springer, 2022)
By a lack of support, appreciation, and understanding, many expressions and manifestations of intangible cultural heritage are under threat, endangered by globalization and cultural homogenization. Intangible cultural heritage has risks becoming lost forever or frozen as a practice belonging to the past if not raised in the community. To strengthen the intangible cultural heritage keeps it alive and continuity, preserving this heritage and passing it on to future generations, and allowing it to change and adapt to any situation. Quality education as a Sustainable Development Goal number 4 (SGD 4) has identified a critical priority in investigating the role of intangible cultural heritage in expanding Education for Sustainable Development. Safeguarding intangible cultural heritage can effectively contribute to sustainable development within each economic, social, and environment while also contributing to peace and security. This paper provided the literature review as an analysis method with a rationalistic approached and discussed the Living Heritage Site Conservation Education for the Community-based in Penang (Malaysia), Singapore, Philippine, and Europe. It is important to note that any efforts to conserve the intangible cultural heritage should be aimed not only at development benefits; the most important thing is to comprehend the local people’s needs. It is indispensable to promote public awareness of intangible cultural heritage conservation protection toward sustainable development using education programs to achieve cultural heritage conservation efficiency. In conclusion, the key a quality education, which brought in the Community-based Education for Living Heritage Conservation, fulfills people’s needs and helps link and empower both local people and the community to conserve the living heritage successfully.